IN VITRO ANALYSIS OF ANTICANCER POTENTIAL OF TRIGONELLA FOENUM-GRAECUM - SINGH, SHIVSHARAN; SATISH K VERMA; SANTOSH SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The recent work was carried out to evaluate the presence of bioactive compounds and anticancer activities of selected plant Trigonella foenum-graecum extract. Methods: The crude extraction of whole plant was carried out using petroleum ether as a solvent by cold percolation as well as hot percolation method (Soxhlet method) both. The presence of phytochemicals was determined using standard protocols. The anticancer activities were evaluated by sulforhodamine B (SRB) dye assay method using Mitomycin-C (anticancer drug) as a positive control. Results: The qualitative analysis of plant extract showed the presence of bioactive compounds, namely, protein, alkaloids, steroids, phenolics, and flavonoids. The plant extract was tested for in vitro anticancer activity against human liver cancer (HEP-2) and colon cancer (HT-29) cell lines using SRB assay. The plant extract showed significant results against HT-29 and HEP-2 cancer cell lines. Conclusion: The study concluded that the extract of T. foenum-graecum can be further carefully used in herbal formulations for cancer therapy.